THE USE OF OUTDOOR GAMES IN IMPROVING THE PHYSICAL FITNESS OF YOUNG VOLLEYBALL PLAYERS (Scientific journal of the Fergana State University, 2025)
This article is written on the topic “The use of outdoor games in improving the physical fitness of young athletes” and explores the importance of outdoor games in the process of physical training of young athletes. The article analyzes the role of outdoor games in physical development, the formation of skills and abilities, increasing the motivation of athletes. The results of questionnaire studies are presented, which show that games are useful for young athletes. The article also provides recommendations on how to effectively integrate outdoor games into physical training programs. The results of this study are important in the field of sports education and physical education, contributing to the further improvement of the training process for young athletes.